Complying with Reasonable Accommodation Requirements for Persons with Visual Impairment in Uganda Public Service Employment? Assumptions and Gaps - Iyundhu, Andrew; Karooma, Cleophas; Emong, Paul (Advances in Social Sciences Research Journal, 2021)
Uganda has got legal and policy frameworks that guarantee the provision of reasonable accommodation in employment for persons with disabilities, persons with visual impairment inclusive. The available literature indicates that persons with visual impairment remain largely disadvantaged in public service employment despite the progressive disability legal and policy framework in the employment. The paper examines the Uganda public service employment compliance with provisions of reasonable accommodation for persons with visual impairment. This paper arises from a study on access to and inclusion of persons with visual impairment in public service employment in Uganda. The study adopted a qualitative research approach. Twenty-two [22] participants were interviewed and included persons with visual impairment in public service and their direct supervisors from four districts of Jinja, Kampala, Iganga, and Mbarara, officials from Public Service Commissions, National Council for Disability, and Uganda National Association of the Blind. Data was obtained using interviews and observation and analyzed using thematic analysis. The results show the gaps and assumptions in the provision of reasonable accommodation requirements for persons with visual impairment in employment and have effects in the provision of auxiliary and support services, modification of working environment & facilities, making information accessible, modification of job application procedures, restructuring work systems, provision of housing, among others.